Pengaruh Media Tanam dan Pupuk Kotoran Ayam Terhadap Pertumbuhan Semai Meranti Merah (Shorea leprosula) - Pebriandi, Pebriandi; Haliyani, Risda; Mardhiansyah, Muhammad (INDIGENOUS BIOLOGI : JURNAL PENDIDIKAN DAN SAINS BIOLOGI, 2023)
Shorea leprosula is one of the most important commercial timber in Indonesia. The existence of this red meranti plant is included in the IUCN Red List with an endangered conservation status. Efforts to increase the productivity of red meranti plants can be done by improving the quality of the planting media and increasing the growth of seedlings. This study aims to determine the effects and the best composition of planting media and chicken manure on the growth of red meranti seedlings. The research was conducted at the Experimental Garden and Forestry Laboratory, Faculty of Agriculture, University of Riau. The method used in this research is a completely randomized design (CRD) factorial pattern consisting of 9 treatments and 3 replications so that 27 experimental units were obtained. The first factor is the concentration of planting media (B) consisting of 3 levels, namely: peat (B1) = 100%, minerals (B2): 100%, combination of peat + minerals = 50% + 50%. The second factor is the concentration of poultry manure (P) consisting of 3 levels, namely: P1 = 10%, P2 = 20%, P3 = 30%. The results showed that the combination of peat and mineral (B3) planting media significantly increased the height of red meranti seedlings with an average of 0.731 cm and a root crown ratio of 3.972. The treatment of poultry manure had no significant effect on the observed parameters of the red meranti seedlings. The best treatment combination was found in the B3P2 combination with an average increase in height of 0.860 cm, diameter increase of 0.089 mm, dry weight of 5.190 g, root crown ratio of 4.770.